Plasmodium falciparum Knockout for the GPCR-Like PfSR25 Receptor Displays Greater Susceptibility to 1,2,3-Triazole Compounds That Block Malaria Parasite Development - Benedito M. dos Santos; Daniel T. G. Gonzaga; Fernando C. da Silva; Vitor F. Ferreira; Celia R. S. Garcia (Biomolecules, 2020)
The search for new compounds with antimalarial activity is urgent, as resistance to ones in the classical drug, has already been described in more than one continent. Compounds derived from 1,2,3-triazoles are effective against parasites and bacteria. Here, we evaluated the potential antimalarial activity against the human malaria parasite Plasmodium falciparum in a culture of fifty-four triazole compounds derived from 1H-and 2H-1,2,3-triazole. We identified thirty-one compounds with potential antimalarial activity at concentrations in the micromolar order (µM) and IC50 values ranging from 2.80 µM (9) to 29.27 µM (21). Then, we selected some of these compounds to perform the same tests on the PfSR25- strain (knockout for P. falciparum G-protein coupled receptor-like, SR25). Our experiences with the PfSR25- strain showed that both compounds with higher antimalarial activity for the 3D7 strain and those with less activity resulted in lower IC50 values for the knockout strain. The cytotoxicity of the compounds was evaluated in human renal embryonic cells (HEK 293), using MTT assays. This demonstrated that the compounds with the highest activity (9, 13, 19, 22, 24, 29), showed no toxicity at the tested concentrations.